Residual low ADC and high FA at the resection margin correlate with poor chemoradiation response and overall survival in high-grade glioma patients. Issue 3 (March 2016) - Qu, Jinrong; Qin, Lei; Cheng, Suchun; Leung, Katherine; Li, Xiang; Li, Hailiang; Dai, Jianping; Jiang, Tao; Akgoz, Ayca; Seethamraju, Ravi; Wang, Qifeng; Rahman, Rifaquat; et al.
Highlights: Resection margin ADC (rmADC) correlates with survival in HGG patients. Low rmADC correlates with shorter overall survival. rmADC correlation with survival is stronger in non-enhancing than enhancing tumor. Pre- chemoradiation ADC correlates better with OS than change in ADC during RT. Abstract: Purpose: We hypothesized that ADC and FA of enhancing tumor (ET) and/or non-enhancing tumor (NT) adjacent to the operative resection margin before and during temozolomide and/or chemoradiation may allow prediction of chemoradiation response and patient survival. Material and methods: DTI was acquired in 37 patients with newly diagnosed HGG at two time points: after resection at the time of pre-RT planning MRI (Baseline) and after 30 Gy of radiation therapy (mid-RT). ADC and FA at each time point and change in ADC and FA between the two time points were assessed by hot spot method in both residual ET and NT within 2 cm of the resection margin and correlated with overall survival (OS) using receiver operating characteristics (ROC) area under curve (AUC) analysis and log-rank testing. Results: At baseline NT ADC < 104 × 10 −5 mm 2 /s was strongly correlated with shorter 15 month OS (95% CI: 227–412 days vs 492–695 days) compared to patients with higher ADC (AUC 0.82). There was good separation between the groups and significance at log-rank testing ( p = 0.0002). Baseline NT FA > 0.257 also correlated with shorter OS (95% CI: 300–515 days vs 438–686 days), compared with patients with lower FA (AUC 0.74), but there was considerable overlap between the groups and non-significance at log-rank testing ( p = 0.089). Residual ET ADC increased significantly ( p = 0.0004) and FA decreased significantly ( p = 0.03) for all patients during early RT but the change in ADC and FA was less strongly correlated with OS than baseline NT metrics. Conclusion: Post-operative pre-radiation baseline low ADC in non-enhancing tumor at the resection margin correlates strongly with worse treatment response and decreased overall survival in a heterogeneous sample of high grade glioma patients treated with radiation and/or temozolamide chemoradiation.